Analysis of the Influence of Adhesive, Geometry, and Manufacturing Processes on Mixed Mode Stress Ratio in Single Lap Shear Adhesive Joint Structures of Aluminum and Composite Plates - Asep Kurnia; Bambang Kismono Hadi; Hendri Syamsudin; Muhamad Giri Suada (Postgraduate, University of Mataram, 2024)
In aircraft structures, composite plate joints often present significant challenges. Mechanical fastenings such as pins, bolts, or rivets require holes to be drilled in the plates, which reduces the strength of the laminate due to stress concentrations around the hole edges. These joints frequently become sources of structural failure in aircraft. Therefore, the design of composite plate joints is crucial to maintain structural integrity. Adhesive joints offer several advantages over mechanical joints, including the ability to join two different materials, more uniform stress distribution along the joint, and reduced weight since no bolts or rivets are needed. The most common adhesive joint design is the Single Lap Joint (SLJ), which is popular due to its simple geometry and high structural efficiency. However, the main drawback of the SLJ is load eccentricity, which leads to secondary bending and undesirable normal stresses along the adhesive edges. The hypothesis of this study is that SLJ conditions with optimal shear strength can be achieved through the right combination of adhesive type, bond surface preparation, and joint configuration. This study analyzes the influence of various adhesive materials, joint designs, and manufacturing methods using numerical modeling methods, validated with analytical approaches and ASTM standard testing. Numerical modeling is conducted using the finite element method with a cohesive zone model (CZM) approach to examine stress distribution in various cases, such as the impact of geometry, adhesive thickness, and joint length. The normal and shear stress distribution along the joint is found to significantly affect the strength of the SLJ, highlighting the importance of careful design and material selection in these applications.